Justification on the selection of revised edition of bloom's taxonomy in the levels of oral questioning in the process of teaching mathematics in Malaysia - Sulaiman, Tajularipin; Mohd Ayub, Ahmad Fauzi; Md Yunus, Aida Suraya; Mahmud, Muhammad Sofwan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This paper discusses a few taxonomies in education that are frequently used in various studies. Although there are other types of taxonomy that have been used by researchers in exploring the cognitive domain of the learning processes such as SOLO Taxonomy, Fink's Taxonomy and Marzano Taxonomy, yet the use of the Revised Edition of Bloom's Taxonomy was considered as the most justified for the study on the cognitive levels of oral questioning used by teachers in the teaching of mathematics. This paper will highlight comparison between all of these taxonomies and further justify the researcher's selection of the Revised Edition of Bloom's Taxonomy according to the suitability and needs of the study as well as the educational trends in Malaysia.